2007
DOI: 10.1177/105268460701700501
|View full text |Cite
|
Sign up to set email alerts
|

Preparing First-Time Leaders for an Urban Public School District: An Action Research Study of a Collaborative District–University Partnership

Abstract: This article reports the results for the first cycle of an action research study about a district-university partnership. Two district facilitators and two university facilitators co-constructed a principal preparation program for an innercity school district to help prepare the next generation of building leaders. Twenty-two students participated in the 15-month nontraditional program. The study found that in preparing first-time school leaders, the most helpful experiences were those that developed self-unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…To address these criticisms, many leadership preparation programs across the country are revising their curriculum and developing school-university partnerships (Fenwick, 2000;Mitgang, 2008;Simmons et al, 2007). School systems also are grooming future school leaders using "succession planning" programs intended to provide meaningful leadership experiences for teachers who aspire to the principalship (Scott, 1999).…”
Section: Implications For Leadership Preparationmentioning
confidence: 98%
“…To address these criticisms, many leadership preparation programs across the country are revising their curriculum and developing school-university partnerships (Fenwick, 2000;Mitgang, 2008;Simmons et al, 2007). School systems also are grooming future school leaders using "succession planning" programs intended to provide meaningful leadership experiences for teachers who aspire to the principalship (Scott, 1999).…”
Section: Implications For Leadership Preparationmentioning
confidence: 98%
“…An emerging literature examines the outcomes of effective partnerships, mostly from student and graduate perceptions. Students perceive opportunities to connect theory and practice (Borden, Preskill, & DeMoss, 2012, using quantitative and qualitative data from end of class and end of course questionnaires and evaluations), gains in leadership knowledge and skills, opportunities for advancement (e.g., Orr & Barber, 2007, comparative study), greater program quality, stronger role for districts (Orr, 2011; Orr & Orphanos, 2011; and the case study design of Korach, 2011), and self-understanding and readiness for role change (Simmons et al, 2007, using an action research approach).…”
Section: Program Elementsmentioning
confidence: 99%
“…Implementation studies were also found in the program evaluation literature. This literature conducted as descriptive studies or using surveys, interviews, documents, and observations focused on the implementation of university–district partnerships (Browne-Ferrigno, 2011; Korach, 2011; Simmons et al, 2007), program design (Browne-Ferrigno, 2013; Kochan & Reames, 2013; Reed & Llanes, 2010), and pilot programs (Schmidt-Davis, 2009).…”
Section: Program Elementsmentioning
confidence: 99%
“…As agents of the school district and the state, they were expected rely on conceptions of schooling that are not designed for equitable outcomes. Simmons et al (2007) report that research has documented that the current high-stakes accountability environment "can impede good principal practices" (p. 542-543). The disjunction that participants in F schools experience between working within, while attempting to change, inequitable institutions was compounded by the micro-management inherent in accountability measures that limit possibilities for democratic participation is schools.…”
Section: Discussionmentioning
confidence: 95%